Taxation in Tanzania - Jörgen Levin (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
Tanzania has during the past years made substantial progress in stabilising the economy. One of the major issues has been to cut down on government activities and there has been a remarkable contraction. Although tax reform has been an important component in Tanzania's economic reform programme the domestic revenue-GDP ratio has remained low. Some of the factors behind the decline in the tax-GDP ratio over the past years are substantial reductions in external taxes, relative large tax incentives for new investments, downsizing of the parastatal sector and sluggish private sector growth. Preliminary results on tax incidence among ten different household groups shows that poorer households paid indirectly a relative large share of import duties. With regard to income taxes the tax rate is high among the poorer households then fall and rise as households become richer. In the longer term Tanzania needs to significantly increase domestic revenue to finance its development programme. Projecting tax revenue, keeping the rates unchanged, we found that towards the end of the period (2004) the tax revenue-GDP ratio reached 17 percent. An alternative option to generate additional revenue would be to increase the tax rates. This does not seem to be a viable strategy. Compared to estimates in other countries the cost of raising an additional shilling is extremely high in Tanzania.
Keywords: O23; O55; H20; 330; fiscal policy; taxation; Tanzania; sub-Saharan Africa; Finanzpolitik; Steuersystem; Tansania